Old Church Slavonic Terminology of Winegrowing and Winemaking: Origin and Development - Villnow Komárková , Jana (Slavia Centralis, 2023)
The topic of the paper is Old Church Slavonic terms from the semantic fields winegrowing and winemaking. Examples of the mentioned terms are taken from Old Church Slavonic literary monuments and are further in the study etymologized. The words documented in Old Church Slavonic texts allow for an accurate picture of how the ancestors of contemporary Slavs cultivated grapes, how they produced wine, and which types of wine they knew and consumed. On the one hand, the origin of the discussed terms attests to the antiqueness of Slavic viniculture, while on the other hand, it provides insight into how terminological systems are formed and developed.
Keywords: etymology, Old Church Slavonic, Proto-Slavic, vinicultural terminology, viticultural terminology